PENGARUH PROGRAM 1000 HARI PERTAMA KEHIDUPAN TERHADAP PRILAKU IBU DALAM PERAWATAN ANAK - Putu Susy Natha Astini; Ni Nyoman Hartati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
The purpose of this research to know about The Effect of first 1000 Days of Life Program on Behavior of Mother in children care.This research used Quasi Experimental with non randomized Control Group Pretest Posttest Design. This study was conducted in Kubu Bangli, from June to October 2017, with sample 64 mothers with children under 2 years. Sampling technique is purposive sampling. Data Analysis used paired t-test and independent sample t-test. Before they have trained the treatment group and control have score less, but after trained the treatment group have score better than control, paired t test with significance α =0,05, obtained p value = 0,00010,05 means significant pre and post comparison of each group. Result show the independent samples test with p value = 0.00010,05 means there is significant influence of 1000 Days of Life Program on mother’ s behavior in children care. The advice is given that the mothers can apply their knowledge, attitude, and skills in caring for their children so that the children become healthy optimally.